2017
DOI: 10.1016/j.yjmcc.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

A model of cardiac contraction based on novel measurements of tension development in human cardiomyocytes

Abstract: Experimental data from human cardiac myocytes at body temperature is crucial for a quantitative understanding of clinically relevant cardiac function and development of whole-organ computational models. However, such experimental data is currently very limited. Specifically, important measurements to characterize changes in tension development in human cardiomyocytes that occur with perturbations in cell length are not available. To address this deficiency, in this study we present an experimental data set col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
150
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 110 publications
(153 citation statements)
references
References 67 publications
3
150
0
Order By: Relevance
“…Our previously published ventricular model [24], when driven by an atrial calcium transient, produces a TPT = 113 ms, RT 50 = 96 ms, compatible with the measurements by Brixius et al Note that due to the differences in calcium kinetics, peak tension in the atria is marginally lower than in the ventricles. We consider this difference of 15-20% to be physiologically plausible, due to lower pressures in the atria (See Figure 2C) = 0.86 µM, resulting in TPT = 82 ms, RT 50 = 75 ms.…”
Section: Atrial Contraction Modelsupporting
confidence: 88%
See 3 more Smart Citations
“…Our previously published ventricular model [24], when driven by an atrial calcium transient, produces a TPT = 113 ms, RT 50 = 96 ms, compatible with the measurements by Brixius et al Note that due to the differences in calcium kinetics, peak tension in the atria is marginally lower than in the ventricles. We consider this difference of 15-20% to be physiologically plausible, due to lower pressures in the atria (See Figure 2C) = 0.86 µM, resulting in TPT = 82 ms, RT 50 = 75 ms.…”
Section: Atrial Contraction Modelsupporting
confidence: 88%
“…To circumvent this uncertainty and variability surrounding the atrial calcium transient in computational models, we use experimentally measured calcium transient data from Brixius et al [6], offset by the local activation time described in the previous section. As this data has not been calibrated, we assume peak and diastolic calcium levels of 0.6 µM and 0.1 µM respectively, based on the ranges seen in computational models [42] and ventricular myocytes [24]. The resulting calcium transient based on calibrating, smoothing and extrapolating the experimental data can be seen in Figure 2A, compared to several recent computational models.…”
Section: Atrial Contraction Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive review articles can be found in Göktepe et al, Clayton et al, and Finka for electrophysiology, solid mechanics, and ECC single problems, respectively. To summarize, the electrophysiology models range form the phenomenological two variable Fitzhugh‐Nagumo model to multi‐ion‐channel cell models that include ECC . For the solid mechanics portion, exponential energy functions are generally used due to the simplicity in parameter estimation .…”
Section: Introductionmentioning
confidence: 99%